Underdiagnosis of depression in an economically deprived population in Macao, China. (21st August 2015) - Lao, Cheng‐Kin; Chan, Yok‐Man; Tong, Henry Hoi‐Yee; Chan, Alexandre
Abstract: Introduction: Previous literature revealed an association between low income and depression. Despite the availability of effective treatments, depression is often underdiagnosed and undertreated. This study was designed to evaluate the prevalence of depressive symptoms and their impact on health‐related quality of life (HRQoL) in a low‐income population in Macao. Methods: This cross‐sectional study targeted the adult beneficiaries of local food bank program. The program was established to provide food assistance to the residents who had low income but were ineligible for government financial assistance. All data were collected through interview and questionnaires. The Patient Health Questionnaire (PHQ‐9) was used for assessing depressive symptoms. Information about depression diagnosis was obtained by the self‐report method. HRQoL levels were measured by the 12‐item Short‐Form Health Survey, Version 2.0. Results: A total of 272 study participants were included for analysis. Based on the PHQ‐9 scores, 27.6% of the participants suffered from moderate to severe depressive symptoms. Among them, 76% were not diagnosed with depression. Those with moderate to severe depressive symptoms had significantly lower levels of HRQoL ( P  < 0.001). Anxiety disorders (OR = 9.71, 95% CI = 2.36–40.06), migraine (OR = 3.88, 95% CI = 1.55–9.73), and poor to fair self‐rated health (OR = 6.30, 95% CI = 1.95–20.40) were the independent factors associated with moderate to severe depressive symptoms. Discussion: Underdiagnosis of depression was prevalent in this low‐income population. There is a need to raise their awareness of mental disorders and improve their access to mental health services.